Ricerche sull'organizzazione del territorio nella Liguria medievale - Paola, Guglielmotti (Reti Medievali E-Book, 2005)
The organisation of the territory is the outcome of strategies of varying scope, in which a number of agents interact to shape out the areas of operation. The Liguria reality is probed here through four different situations - separated in chronological terms but sharing the poor visibility and limited efficacy of the fortified settlements. These focus on Genoa, both in the definition of its hinterland between the tenth and the eleventh centuries, and in establishing the bulwarks of coastal territorial expansion in the twelfth; the powerful groups of feudal lords who remoulded the rural settlement layout in the thirteenth century; finally, a village of the hinterland explored right through to the modern age.